Microsatellite DNA Instability and Loss of Heterozygosity in Pulmonary Sarcoidosis - VASSILAKIS, DIMITRIS A.; SOURVINOS, GEORGE; MARKATOS, MILTIADIS; PSATHAKIS, KOSTAS; SPANDIDOS, DEMETRIOS A.; SIAFAKAS, NIKOLAOS M.; BOUROS, DEMOSTHENES (American journal of respiratory and critical care medicine, 1999)
In the present study we investigated the incidence of microsatellite instability (MI) and loss of heterozygosity (LOH) in sarcoidosis, a multisystem disease of unknown origin. We examined sputum cytological specimens from 30 patients with sarcoidosis and 30 healthy, matched subjects, using 10 highly polymorphic microsatellite markers located at several chromosomal arms. The electrophoretic pattern of each specimen was compared with the corresponding pattern of peripheral blood and any difference in the mobility of the microsatellite alleles was interpreted as MI-positive. LOH was scored as decrease in intensity of one allele relative to the other as determined from comparison of sputum and normal (blood) DNA. We found that 14 (47%) sarcoidosis patients showed genetic alterations, either MI or LOH. Six (20%) patients exhibited MI and nine (30%) exhibited LOH in at least one microsatellite marker. One of the patients exhibited MI in two microsatellite markers and three (10%) showed LOH in more than one marker. One patient showed complete deletion of the chromosomal arm 17q11.2-q21. None of the healthy subjects exhibited any genetic alteration in the studied markers. No correlation was found between the genetic alterations detected and age, disease duration, blood gases, or spirometric parameters of the patients. Our findings suggest that MI is a detectable phenomenon in sarcoidosis and seems not to be related with the severity of the disease. The detection of LOH indicates the presence of putative tumor suppressor genes at loci examined, which may play an important role in the etiopathogenesis of sarcoidosis.